2020
DOI: 10.7717/peerj.8562
|View full text |Cite
|
Sign up to set email alerts
|

The E2F family as potential biomarkers and therapeutic targets in colon cancer

Abstract: Background The E2F family is a group of genes encoding a series of transcription factors in higher eukaryotes and participating in the regulation of cell cycle and DNA synthesis in mammals. This study was designed to investigate the role of E2F family in colon cancer. Methods In this study, the transcriptional levels of E2F1-8 in patients with colon cancer from GEPIA was examined. Meanwhile, the immunohistochemical data of the eight genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…We discovered that E2F2 and E2F7 knockdown suppressed proliferation and migration abilities, promoted cell cycle arrest, and inhibited stemness of both HeLa and C-33 A cells in vitro, suggesting that E2F2 and E2F7 may function as oncogenes, leading to tumor progression or metastasis of HPV-positive and HPV-negative cervical cancer. In line with the possible role of E2Fs in human tumorigenesis, previous studies have shown overexpression of E2Fs in several human malignant tumors at both the mRNA and protein level [26][27][28][29][30][31]. Importantly, in the current study, we show evidence of an association between E2F1/2/7/8 with histological grade, lymph node metastasis, lymph vessel invasion, and deep invasion of cervical stroma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We discovered that E2F2 and E2F7 knockdown suppressed proliferation and migration abilities, promoted cell cycle arrest, and inhibited stemness of both HeLa and C-33 A cells in vitro, suggesting that E2F2 and E2F7 may function as oncogenes, leading to tumor progression or metastasis of HPV-positive and HPV-negative cervical cancer. In line with the possible role of E2Fs in human tumorigenesis, previous studies have shown overexpression of E2Fs in several human malignant tumors at both the mRNA and protein level [26][27][28][29][30][31]. Importantly, in the current study, we show evidence of an association between E2F1/2/7/8 with histological grade, lymph node metastasis, lymph vessel invasion, and deep invasion of cervical stroma.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have similarly reported an association between increased expression of E2Fs and high-risk clinicopathological factors in lung carcinoma [ 32 ], breast cancer [ 7 ], clear cell renal cell carcinoma [ 33 ], and non-muscle invasive bladder cancer [ 34 ]. In ovarian cancer, it was found that E2F1/2/5/8 are poor prognostic biomarkers and therapeutic targets [ 35 ]]; in contrast, Yao et al demonstrated that E2F1/2/3/5/7/8 are potential biomarkers for the diagnosis of colon cancer and E2F3/4/7/8 are potential targets of precision therapy [ 28 ]. In the current study, we found that genetic mutations in E2Fs are associated with poor DFS in cervical cancer, a finding that may be accounted for by Shan et al [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is regarded as one of the primary reasons of mortality associated with cancers the world over ( 18 ). The E2F family is a gene group encoding a series of transcription factors in higher eukaryotes, which may participate in mammalian cell cycle regulation and DNA synthesis ( 6 ). Findings obtained from a previous study suggest that E2F1 and E2F7 have different regulatory effects on KPNA2 to promote the development of gallbladder cancer ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…E2F transcription factor 7 (E2F7) exerts tumor suppressive role by suppressing the transcription level of genes that participated in the entry of S-phase and disease progression ( 5 ). E2F7 is among the potential targets for molecular-based treatment of colon cancer patients ( 6 ). E2F7 modulates transcription and maturation of various microRNAs (miRNAs), which could regulate gene expression post-transcriptionally, to inhibit cell proliferation ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, based on the aforementioned analysis, the present study identified an intersection between the mRNAs predicted by lncRNAs and sequencing DE mRNAs. The results presented the 236 intersection mRNAs (Table SII), and certain of them have been affirmed as cancer-associated genes, for instance CDK1, CCNB1, BUB1, EGF, E2F1, E2F2, FEN1, CD36, PARP1 and EFNA1 (33,34).…”
Section: Prediction Of Mirna Binding Sites Cerna and Ppi Network Conmentioning
confidence: 84%